Writing anxiety in online context: qualitative approach - Kamaruddin, Siti Faridah (UiTM Sarawak, 2021)
Writing anxiety is a phenomenon that majority of ESL students experience. However, when the traditional writing classroom shifted to online distance learning due to the Covid-19 pandemic, writing anxiety among students reached new heights. In addressing this issue, this qualitative study explored the reported experiences of nine students from the Diploma in Banking Studies (BAI 19) based in UiTM Mukah Campus. The nine subjects had registered with ELC23 Ifor the Mac - July 2020 semester, and the course was taught online.